Profiles of deliberate and accidental self harmers admitted in hospitals in Malaysia Project Report (PRODASH) - Gani F.D.A.; Alias N.; Hussin S.; Ahmad Z.; Ali N.; Haniff J.; Bakar L.; Tajjudin I.; Nor N.U.M. (UPM Press, 2024)
Mal J Med Health Sci 15(3): 81-88, Oct 2019